2017
DOI: 10.1021/acsami.6b15064
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated and Functionalized Aliphatic Polycarbonate Polyplex Nanoparticles for Intravenous Administration of HDAC5 siRNA in Cancer Therapy

Abstract: Guanidine and morpholine functionalized aliphatic polycarbonate polymers able to efficiently deliver histone deacetylase 5 (HDAC5) siRNA into the cytoplasm of cancer cells in vitro leading to a decrease of cell proliferation were previously developed. To allow these biodegradable and biocompatible polyplex nanoparticles to overcome the extracellular barriers and be effective in vivo after an intravenous injection, polyethylene glycol chains (PEG 750 Hemocompatibility tests showed no effect of these polyplexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…Moreover, such new PC vectors were modified with PEG chains on their polymeric structure, followed by complexing with siRNA to form polyplexes. 123 Such modification successfully overcame the extracellular barriers, thus resulting in effective in vivo results after an intravenous injection. Results showed that the polyplexes exhibited no significant influence on hemolysis and coagulation.…”
Section: Polycarbonatesmentioning
confidence: 99%
“…Moreover, such new PC vectors were modified with PEG chains on their polymeric structure, followed by complexing with siRNA to form polyplexes. 123 Such modification successfully overcame the extracellular barriers, thus resulting in effective in vivo results after an intravenous injection. Results showed that the polyplexes exhibited no significant influence on hemolysis and coagulation.…”
Section: Polycarbonatesmentioning
confidence: 99%
“…miRNAs are known to be involved in cancer progression, invasion and metastasis wherein their levels are either upregulated or down regulated. miRNAs as therapeutic tool in cancer has been explored by several research groups which have shown improved outcome in terms of increased cytotoxicity, decreased invasion and metastasis. ,,, Delivery strategies including nanoplexes, polyplexes, lipoplexes, micelleplexes , and dendriplexes have been reported for miRNA delivery since naked miRNAs could not penetrate the bilayer lipidic membrane because of high molecular weight, hydrophilic and anionic nature and instability in biological milieu. Apart from effectively complexing miRNAs and protecting them from degradation, another important requirement for ideal delivery system is that they should be able to improve the uptake of miRNA by cancer cells followed by their successful endosomal escape and release into the cytoplasm so that they can get into the RISC assembly for effective mRNA degradation and/or translation repression …”
Section: Discussionmentioning
confidence: 99%
“…Some studies illustrate the strong differences between the in vitro and in vivo results. Among them, one recurring issue is PC, in particular its screening effect hindering the interactions between NPs and their targets 135,136 . Hadjidemetriou and co-workers studied the in vivo behavior of PC on liposomal NPs.…”
Section: In Vivo Analysis Of Pc: In Vitro and In Vivo Measurements Armentioning
confidence: 99%